2021
DOI: 10.3390/polym13101618
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Synthesis Route of Hybrid Polyurea-Polyurethane-MWCNTs Nanocomposite Coatings for Ballistic Protection and Experimental Testing in Dynamic Regime

Abstract: This study describes a simple, practical, inexpensive, improved, and efficient novel method for obtaining polyurea-polyurethane-multiwall carbon nanotubes (MWCNTs) nanocomposites with enhanced mechanical properties, and their experimental testing in a dynamic regime. SEM and micro-CT investigations validated the homogeneity of the nanocomposite films and uniform dispersion of the nanofiller inside the polymeric matrix. The experimental measurements (TGA, DSC, DMA, and tensile tests) revealed improved thermal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…PU coating could significantly increase the resistance of conventional ceramic/metal armor to create a new armor system without adding extra weight [ 47 ]. In one of our previous studies [ 48 ], we demonstrated that PU–PUR-coated aluminum plates maintained their integrity at impact with a projectile. Many other studies emphasize the advantages of high-performance PU–PUR materials for ballistic protection applications, and a few examples are provided below.…”
Section: Introductionmentioning
confidence: 84%
“…PU coating could significantly increase the resistance of conventional ceramic/metal armor to create a new armor system without adding extra weight [ 47 ]. In one of our previous studies [ 48 ], we demonstrated that PU–PUR-coated aluminum plates maintained their integrity at impact with a projectile. Many other studies emphasize the advantages of high-performance PU–PUR materials for ballistic protection applications, and a few examples are provided below.…”
Section: Introductionmentioning
confidence: 84%
“…Moreover, p-CDEA-substituted foam samples reveal a unique thermal transition ranging from −17 °C-20 °C, vastly different from the PU-V490 control. This transition might be attributed to the glass transition temperatures of urea segments 48 which in Fig. 11 showed a consistently increasing enthalpy change as p-CDEA concentration is increased in the foam formulation.…”
Section: Poly(urethane-urea) (Pua) Foam Synthesis and Propertiesmentioning
confidence: 92%
“…Herein, we focus on a polyurea (PU) formed by the reaction of a diisocyanate and diamine [ 37 , 38 ]. Molecularly, it is similar to polyamide, but has a structure where significant hydrogen bonding occurs between the polymer chains, enhancing the mechanical properties [ 39 , 40 ]. Recently, the use of PUs in films, foams, and composites, such as vertical body panels, spray foams, and microcellular foam liquid plastics, has attracted attention in industrial applications [ 41 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%